Physiological adaptations following resistance training in youth athletes—A narrative review - Legerlotz, K.; Marzilger, R.; Bohm, S.; Arampatzis, A. (Pediatric Exercise Science, 2016)
Purpose: To understand the mechanisms for the effects of resistance training on functional parameters, and to assess the injury risk of the involved tissues, it is necessary to examine the underlying morphological and structural changes of the respective tissues. Methods: The presented information on physiological adaptations have been deduced from cross-sectional studies comparing youth athletes with controls and children with adults as well as from longitudinal studies examining the effects of resistance training in untrained children and adolescents and in youth athletes. Results: The evidence indicates, that training induced changes in motor performance rely partly on enhanced neuromuscular control, and partly on morphological adaptation of muscles and tendons, such as changes in muscle, muscle fiber and tendon cross-sectional area, muscle composition, and tendon material properties, with the bone also adapting by increasing bone mineral content and cortical area. Conclusion: Although the training induced adaptations of the investigated tissues follows similar principles in children as in adults, the magnitude of the adaptive response appears to be more subtle. As studies investigating physiological adaptation in youth athletes are sparse, more research in this area is warranted to elucidate the specific physiological stimulus-response relationship necessary for effective training programs and injury prevention.